Dilute nitride-based photodetectors : fabrication, characterization and performance - Xu, Zhe (2012)
Dilute nitride materials grown on GaAs substrate have shown the potential to act as new material candidates for the optical-fiber communication system. In particular, GaNAsSb has been found to be superior to its predecessor, GaInNAs, due to the possibility of suppressing In-induced N clustering and N-related defects in the material. In this work, high performance photodetectors containing GaNAsSb as the active layer grown on GaAs substrate are demonstrated. The numerical studies show that a high quantum efficiency and a large bandwidth can be achieved by employing a waveguide structure. With a proper propagation distance (~10 µm), the light absorption is efficient and the GaNAsSb layer is applicable to be grown thin enough (~0.4 µm) for a short carrier transit-time. A thin GaNAsSb layer allows a further extension of the absorption edge (reduction of the bandgap) by increasing the N and Sb contents with the compromise of introducing more lattice strain. The use of additional AlGaAs cladding layers enhances the optical confinement and reduces the optical field mismatch between the waveguide and the fiber. GaNAsSb on GaAs waveguide photodetectors (WGPDs) were successfully fabricated in this project. At the 1.3 µm wavelength, high responsivity values of 0.72 A/W and 0.55 A/W were obtained for WGPDs with and without additional AlGaAs cladding layers, respectively. These values corresponded to the very high internal quantum efficiencies of 96.7% and 73.9%, respectively. The optical performance agreed with the numerical studies. The best cut-off frequency was 16.5 GHz for the GaNAsSb/GaAs/AlGaAs WGPD. At the 1.55 µm wavelength, the best responsivity was 0.6 A/W (0.1 mW optical power injection) at -4 V bias. Several GaNAsSb on GaAs WGPDs with different dimensions showed bandwidths over 10 GHz with the best value being 14.3 GHz and a responsivity of ~0.2 A/W at the same time. The combined performances achieved in this thesis are considered the best results for the dilute nitride-based photodetectors for the 1.3 µm and 1.55 µm wavelengths. Further analysis shows that the overall frequency responses were resistance-capacitance time limited. Based on the measurement setup, the small-signal equivalent circuits of the 2-port network are discussed. In this approach, the WGPD is represented by a lumped-element model with its bias dependent resistance and capacitance fitted from the reflection coefficient.